2020
DOI: 10.1007/s40430-020-02618-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal investigation and flow pattern analysis of a closed-loop pulsating heat pipe with binary mixtures

Abstract: The present study basically examines thermal performance and relevant flow phenomena of a flat plate closed-loop pulsating heat pipe (FP-CLPHP) filled with binary mixtures. The heat pipe has eight turns, each of which consisting of asymmetrical channel pairs having cross sections as 2 mm × 2 mm and 1 mm × 2 mm (width × height). Binary mixtures are generated as mixtures of ethanol (E) and pentane (P) with different mixing ratios. Mainly, effects of volume mixing ratio (E/P = 1:1, 1:3 and 3:1), vertical (90°) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…Among all the ethanol–water mixtures, the mixture with 1:1 mixing ratio seems to have the lowest thermal resistance at the most heating power. Markal and Varol investigated the working behavior and cooling performance of an oscillating heat pipe charged with an ethanol–pentane mixtures; they found that using a mixture with a high pentane fraction (i.e., 75%) as working fluid could attain better cooling performance than other mixtures with a lower pentane mixing ratio (25% and 50%).…”
Section: Btmss Based On Oscillating Heat Pipesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the ethanol–water mixtures, the mixture with 1:1 mixing ratio seems to have the lowest thermal resistance at the most heating power. Markal and Varol investigated the working behavior and cooling performance of an oscillating heat pipe charged with an ethanol–pentane mixtures; they found that using a mixture with a high pentane fraction (i.e., 75%) as working fluid could attain better cooling performance than other mixtures with a lower pentane mixing ratio (25% and 50%).…”
Section: Btmss Based On Oscillating Heat Pipesmentioning
confidence: 99%
“…At higher heating powers and larger temperature differences in the evaporator section, using higher filling ratios of 60% or 70% tends to be a more preferable choice in terms of heat transfer and elimination of early dry-out . For binary mixtures, such as ethanol–water mixtures and ethanol–pentane mixtures used in the studies of Wei et al as well as in those of Markal and Varol, the optimum filling ratio is 30% (Figure ). As could be induced from the above studies, the optimum filling ratio obtained for one working fluid could not be used for another, which means that the effects of the filling ratio should be evaluated for different working fluids.…”
Section: Btmss Based On Oscillating Heat Pipesmentioning
confidence: 99%
“…Markal and Varol [148] studied the effects of the volume mixing ratio, inclination angle, and fill ratio on the OHP thermal performance of ethanol (E)-pentane (P) mixtures under different heat inputs. The ethanol-pentane mixture exhibited lower thermal resistance and had the best thermal performance with the filling rate FR of 30%, the dip angle IA of 90 • , and the mixing ratio E:P of 1:3.…”
Section: Liquidsmentioning
confidence: 99%
“…İstenilen debi ve sıcaklıkta akışkanın sürekli akışını sağlayacak şekilde; sabit sıcaklık banyosu, mikro pompa, akış ölçer ve sıcaklık ölçüm elemanlarından (T-tipi termoelemanlar) oluşmaktadır. Deney düzeneği ve sistemdeki cihazlara ait detaylı bilgiler için yazarların önceki çalışmalarına bakılabilir [20]- [22]. Deneylerin yapılışı ve test bölgesine ait detaylar aşağıda belirtilmiştir.…”
Section: A Deney Düzeneği̇ Ve Test Bölgesi̇unclassified
“…Kartuş ısıtıcılar, bir güç kaynağı ile bağlantılı olup, PHP hassas bir şekilde istenilen ısıl güç değerine maruz bırakılabilmektedir. hesaplama adımları, atımlı ısı borusu literatüründe[11],[23], genel kabul gören ve yazarların önceki çalışmalarında da[20]-[22] belirtilen formda sunulmuştur. Bu kapsamda, bir PHP'nin en önemli ısıl performans göstergelerinden biri toplam ısıl direnç veya sadece ısıl direnç olarak adlandırılan terimdir ve aşağıdaki gibi hesaplanır: Te ve Tc, sırasıyla, buharlaştırıcı ve yoğuşturucudaki termoelemanlardan okunan sıcaklıkların ortalamasını, bir başka ifade ile ortalama buharlaştırıcı ve yoğuşturucu sıcaklıklarını temsil etmektedir.…”
unclassified